Social Marketing Intervention to Engage Older Adults in Balance Workshops for Fall Prevention: A Multicenter Quasi-Experimental Protocol Study - Goethals, Luc; Barth, Nathalie; Hupin, David; Chapoton, Boris; Guyot, Jessica; Celarier, Thomas; Roche, Frederic; Gallopel-Morvan, Karine; Bongue, Bienvenu (Frontiers in Public Health, 2021)
Background: Falls are a significant source of morbidity in people aged 65 and over, affecting one in three people in this age group. The scientific evidence indicates that physical activity is the most effective method for preventing falls among seniors. Objective: The main objective of this study is to determine whether a Social Marketing Program increases the attendance rate of people aged 60 and over at Group Balance Workshops. Methods: This quasi-experimental multicenter study is being conducted in three French Regions (Loire, Haute-Loire and Rhône) over a period of 18 months. The Social Marketing Campaign will be done in three ways. Firstly, a Communication Campaign will take place in the two Test Areas but not in the Control Area. Secondly, flyers have been designed to be distributed by local partners. Finally, conferences for older people will be organized in the areas of intervention in order to reach the target audience for the program. The study will include people aged 60 and older who want to participate in the Balance Program. Results: The Crédit Agricole Loire/Haute-Loire Foundation funded the study and the Jean Monnet University of Saint-Etienne reviewed it. The Ethics Committee of the University Teaching Hospital of Saint-Etienne approved and peer-reviewed it on September 6, 2019, under Reference Number IRBN622019 / CHUSTE. Conclusion: This first study will demonstrate if a Social Marketing Program based on the promotion of Group Balance workshops among older adults aged 60 and over will increase their attendance rate at sessions on activities-adapted physical skills, and more specifically in those related to fall prevention.